Effects of salinity, temperature, light intensity and light regimes on production, growth and reproductive parameters of Apocyclops dengizicus - Farhadian, Omidvar; Md. Yusoff, Fatimah; Arshad, Aziz (Iranian Fisheries Science Research Institute, 2014)
The effects of salinity, temperature, and light conditions on production and development, longevity, survival and sex ratios of the cyclopoid copepod, A. dengizicus were determined. Seven different salinity levels (5, 10, 15, 20, 25, 30, 35 psu), four temperatures (20, 25, 30, 35 °C), three different light intensities (33.3, 85.3, 162.1 μmol photons/ m2/ s) and light regimes (24:0, 0:24, and 12:12 h light:dark regime) were employed . The highest production was achieved under 20 psu salinity. The optimum temperature required for the maximum reproduction and shortest development time was 35 °C. The production was highest (p<.05) and development rate of A. dengizicus was shortest (p<.05) under the lowest light intensity (33.3 μmol photons/ m2/ s). Continuous light (24:0 h LD) showed positive effects on growth and production. Light regimes 24:0 h and 12:12 h LD yielded the highest total production and growth (p<.05), with highest (p<.05) survival percentage. This study demonstrated that A. dengizicus can tolerate wide range of environmental conditions and can be cultured for commercial live feed purposes as well as toxicity studies.